(untitled) (BIRDEM Medical Journal, 2022)
Background: In healthcare facilities, methicillin-resistant Staphylococcus aureus (MRSA) has long been a common pathogen. Indiscriminate and incomplete uses of antibiotics are creating MRSA more alarming day by day.This study aims to determine the antimicrobial activity of Lannea coromandelica (Jhika or Indian ash tree) bark extract against MRSA. Methods: This experimental study was carried out in Department of Microbiology and Department of Pharmacology, Bangladesh University of Health Sciences, from January to July, 2021. In this study, a bark extract of Lannea coromandelica was prepared by macerating dried powder of the bark of the Jhika or Indian ash tree. Then bark extract was immersed in methanol, ethanol, and water for 48-72 hours, followed by solvent filtering and evaporation. MRSA were identified by biochemical test and then Kibry-Bauer disc diffusion method employed against MRSA isolates using commonly used antibiotics.Then the antibacterial activity of Lannea coromandelica extracts against MRSA was monitored. The microdilution method was used to assess the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of bark extracts. Finally, phytochemical screening was carried out only for methanolic extract. Results: All MRSA isolates were completely resistant to cefoxitin, oxacillin, gentamicin followed by tetracycline. Methanol, ethanol and aqueous extracts of Lannea coromandelica produce maximum zones of inhibition of 14 mm, 13 mm, and 12 mm, respectively, with MIC and MBC values ranging from 3.125 mg/ml to 12.5 mg/ml against MRSA. Phytochemical screening of methanolic extract determined the presence of tannin, saponin, flavonoid, phenol which may be the cause of the highest zone of inhibition against MRSA. Conclusion: It can be concluded that methanol, ethanol and aqueous bark extract of Lannea coromandelica exhibited in vitro antibacterial activity against MRSA by disc diffusion method and detailed pharmacological screening should be carried out for the exploration of effective and natural drugs. BIRDEM Med J 2022; 12(3): 201-206